2008
DOI: 10.1111/j.1532-5415.2007.01600.x
|View full text |Cite
|
Sign up to set email alerts
|

Reaction to a Dementia Diagnosis in Individuals with Alzheimer's Disease and Mild Cognitive Impairment

Abstract: Disclosure of a dementia diagnosis does not prompt a catastrophic emotional reaction in most people, even those who are only mildly impaired, and may provide some relief once an explanation for symptoms is known and a treatment plan is developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
129
0
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 165 publications
(138 citation statements)
references
References 40 publications
(43 reference statements)
5
129
0
4
Order By: Relevance
“…I was informed of her diagnosis, which might help in relieving some of her anxiety. 60 Her husband is instructed in general ways that might help with her anxiety, such as having a predictable routine to the day, simplifying tasks, reducing excess stimulation, and following the 3 R's (repeat, reassure and redirect). 61 For her insomnia, Mrs.…”
Section: Interventions For Behavioural and Psychological Symptomsmentioning
confidence: 99%
“…I was informed of her diagnosis, which might help in relieving some of her anxiety. 60 Her husband is instructed in general ways that might help with her anxiety, such as having a predictable routine to the day, simplifying tasks, reducing excess stimulation, and following the 3 R's (repeat, reassure and redirect). 61 For her insomnia, Mrs.…”
Section: Interventions For Behavioural and Psychological Symptomsmentioning
confidence: 99%
“…Un estudio sobre discusión de diagnóstico de demencia con el paciente, no mostró que se gatillara una reacción emocional catastrófi ca al saber el diagnóstico, incluso podía ser un factor de reducción de ansiedad al tener una explicación de los síntomas y proveer un plan de tratamiento 25 .…”
Section: Principios éTicos Involucradosunclassified
“…It is widely understood that the way bad news is communicated can have a significant impact on the way patients and families adjust to serious illness. It has been found that dementia patients in the general population don't experience a catastrophic emotional reaction when they are told their diagnosis; rather, they experience relief that there is an explanation for their symptoms and that a treatment plan can be developed (Carpenter et al 2008). There is no reason to believe that this would be any different for people with learning disabilities (Watchman 2013).…”
Section: Attitudes To Breaking Bad Newsmentioning
confidence: 99%